Repercussions of the COVID- 19 pandemic on maternal and congenital syphilis in South Brazil: a time series analysis 2010-2022 - Fernando Echegaray; Christopher J. Hernandez; Kavya G. Sundar; Lanbo Z. Yang; Mary Catherine Cambou; Eddy R. Segura; Marineide Gonçalves de Melo; Breno Riegel Santos; Ivana Rosângela dos Santos Varella; Karin Nielsen-Saines (BMC Infectious Diseases)
Abstract Background The global increase in maternal and congenital syphilis cases over the past decade has been substantial. In south Brazil, preexisting maternal and congenital syphilis epidemics have been worsened since the onset of COVID- 19. We evaluated the impact of the COVID- 19 pandemic on the epidemiological trends of maternal and congenital syphilis in Porto Alegre, Brazil. Methods We conducted a retrospective review of hospital records from a large public hospital network, covering the full period of January 1, 2010, to December 31, 2022. Based on historical maternal syphilis and congenital syphilis cases from 2010 to 2019, a Holt-Winters seasonal forecasting model was used to predict maternal syphilis prevalence from 2020 to 2022. A subanalysis of total births, corresponding maternal syphilis prevalence, congenital syphilis cases and infant outcomes was performed for 2017 to 2022 to take a closer look at the years preceding and following the pandemic onset. The diagnoses of maternal and congenital syphilis were determined according to the Brazilian Ministry of Health guidelines. Results The Holt-Winters model predicted relatively stable maternal syphilis prevalence from 2020 to 2022. In contrast, the observed prevalence at delivery was higher than predicted: in 2021 and 2022, forecasting predicted average yearly prevalences of 8.7% and 8.8%, while observed prevalences were 12.5.% and 10.3%. Total births throughout 2017–2022 remained stable with mild decline in the pandemic period. Total maternal syphilis prevalence did not change from 11.1% in 2019 to 2020. However, the percentage of patients diagnosed with syphilis at delivery increased from 14% in 2019 to 65% in 2020. A statistically significant increase in total maternal syphilis prevalence from 11.1% in 2020 to 14.8% in 2021, p ≤ 0.05 was noted. Congenital syphilis diagnoses decreased from 57 to 24% during the pre-pandemic period and increased to 27% in 2022. The incidence of fetal demise in syphilis-positive patients declined throughout the study period from 14% to 6.9% equating roughly 30 cases per year. Conclusion The COVID- 19 pandemic was a significant setback in recent progress made toward the control of maternal and congenital syphilis in south Brazil. Public health strategies should prioritize reinstatement of interventions for prevention of gestational syphilis.